Super mad at everything all the time: political media and our national anger - Dagnes, Alison (Palgrave Macmillan, 2019)
Two truths -- Upping the anti's: 50 years of vilifying intellectuals, the government, and the media -- Money + tech = problems: technological development, financial imperatives, and the ensuing media landscape -- Us vs. them: political polarization and the politicization of everything -- Negative objectives: the right-wing media circle and everyone else -- Consequential, problematic and perhaps resolvable.